The value of network investment coordination to reduce environmental externalities when integrating renewables: Case on the Chilean transmission network. (March 2019) - Matamala, Carlos; Moreno, Rodrigo; Sauma, Enzo
Abstract: The need to decarbonize the power sector through increased participation of renewable generation has originated an escalating necessity for transmission network investments that can be undertaken by a number of market participants, including planning authorities/system operators, network companies and project developers. The expansion of the power network, however, presents various environmental and social conflicts, in particular, with land uses that are valuable by society such as the presence of communities, national parks, protected forests, tourism zones, archaeological sites, etc. In this context of environmental and social awareness, we assess the benefits of two strategies that coordinate network investments among various participants and compare them against the current counterfactual approach, where no coordination is undertaken and thus renewable generation projects are connected to the main transmission system in an individual, project-by-project basis. Through various case studies based on the main Chilean transmission system, we show that the lack of coordination in network investments may present severe impacts in terms of the socio-environmental externalities of transmission network expansions. Furthermore, we demonstrate that attempting to reduce externalities of new network investments without proper coordination of new developments may significantly limit the success of a land use policy associated with network developments. Highlights: The expansion of the power network presents environmental and social conflicts. Three different strategies for coordinating transmission investments associated with new renewable generation are analyzed. There is a limited capability to reduce investment costs and externalities without proper coordination of new investments. More coordination does not necessarily leads (by itself) to lower socio-environmental costs. Appropriate land use policy needs to jointly consider both externality costs and investments coordination.